Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on the Incidence of Shunt-Dependent Hydrocephalus in Infants With Myelomeningocele After Prenatal Versus Postnatal Repair. Issue 3 (16th August 2019) - Tamber, Mandeep S; Flannery, Ann Marie; McClung-Smith, Catherine; Assassi, Nadege; Bauer, David F; Beier, Alexandra D; Blount, Jeffrey P; Durham, Susan R; Klimo Jr, Paul; Nikas, Dimitrios C; Rehring, Patricia; Tyagi, Rachana; et al.
Abstract: BACKGROUND: Myelomeningocele (MM) is a condition that is responsible for considerable morbidity in the pediatric population. A significant proportion of the morbidity related to MM is attributable to hydrocephalus and the surgical management thereof. Postnatal repair remains the most common form of treatment; however, increased rates of prenatal diagnosis, advances in fetal surgery, and a hypothesis that neural injury continues in utero until the MM defect is repaired have led to the development and evaluation of prenatal surgery as a means to improve outcomes in afflicted infants. OBJECTIVE: The objective of this guideline is to systematically evaluate the literature to determine whether there is a difference in the proportion of patients who develop shunt-dependent hydrocephalus in infants who underwent prenatal MM repair compared to infants who had postnatal repair. METHODS: The Guidelines Task Force developed search terms and strategies used to search PubMed and Embase for relevant literature published between 1966 and September 2016. Strict inclusion/exclusion criteria were used to screen abstracts and to develop a list of relevant articles for full-text review. Full-text articles were then reviewed, and when appropriate, included as evidence. RESULTS: A total of 87 abstracts were identified and reviewed by 3 independent reviewers. Thirty-nine full-text articles were selected for analysis. Three studies met selection criteria and were included in the evidence table. CONCLUSION: Class I evidence from 1 study and class III evidence from 2 studies suggest that, in comparison to postnatal repair, prenatal surgery for MM reduces the risk of developing shunt-dependent hydrocephalus. Therefore, prenatal repair of MM is recommended for those fetuses who meet specific criteria for prenatal surgery to reduce the risk of developing shunt-dependent hydrocephalus (level I). Differences between prenatal and postnatal repair with respect to the requirement for permanent cerebrospinal fluid diversion should be considered alongside other relevant maternal and fetal factors when deciding upon a preferred method of MM closure.  The full guideline can be found at https://www.cns.org/guidelines/guidelines-spina-bifida-chapter-2 .